Respuesta :
Answer:
(-3x+30)
Step-by-step explanation:
We first distribute: 4(x+7) = 4x+28
Then, we bring it down.
4x+28-7x=2
Combine like terms.
4x+(-7x) = -3x ... 28+2 = 30.
Combine both results.
-3x+30
Answer:
[tex]-3x+30[/tex]
Step-by-step explanation:
We have been given an expression [tex]4(x+7)-7x+2[/tex]. We are asked to simplify our given expression.
Using distributive property [tex]a(b+c)=ab+ac[/tex], we will get:
[tex]4*x+4*7-7x+2[/tex]
[tex]4x+28-7x+2[/tex]
Combine like terms:
[tex]4x-7x+2+28[/tex]
[tex]-3x+30[/tex]
Therefore, the simplified form of our given expression would be [tex]-3x+30[/tex].